Biotechnology as Factor for The Fourth Generation of Human Rights Formation - Ivanii, Olena; Kuchuk, Andrii; Orlova, Olena (Journal of History Culture and Art Research, 2020)
The development of biology, medicine, and engineering has caused significant social changes that could not but affect the legal regulation of social relations in the field of use of biotechnology. The new opportunities that people received from biotechnology went beyond the classical understanding of human rights and their three generations. Since the last quarter of the twentieth century international organizations have adopted separate international treaties (including those belonging to soft law), the main purpose of which is to prevent the use of biotechnology in cases that could lead to an attack on human dignity. The latter is recognized as the factor determining the boundaries of biotechnology development. The intensive development of biotechnology has led to the emergence of new rights that scientists call somatic, which are suggested to be attributed to the fourth generation of human rights. This generation of human rights is associated with a specific object – the human body and is dependent on the state of development of biology, genetics, medicine, technology, as well as society in general. At the same time, somatic rights affect the development of these areas, limiting (forbidding) the development of those encroaching upon human dignity. It is suggested to classify existing approaches to understanding of somatic rights into four groups: 1) the right to euthanasia, 2) reproductive rights and rights related to the disposal with organs and tissues, 3) rights in the sexual sphere, 4) the right to change sex. The rights in the sexual sphere have an indirect link with the development of biotechnology. Within the European countries there is no single approach to understanding the essence and the list of somatic rights, the legal regulation of their scope varies in each of the states, as evidenced by the practice of the European Court of Human Rights. By the broad discretion of the states in the legal regulation of relations related to the use of biotechnology, it is the theory of the fourth generation of human rights that can be the basis of consensus on the development of biotechnology in order to prevent the loss by a person of himself/herself.